1994
DOI: 10.1021/la00019a017
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Alkyltrimethylammonium Surfactants with Polyacrylate and Poly(styrenesulfonate) in Aqueous Solution: Phase Behavior and Surfactant Aggregation Numbers

Abstract: The interactions between polyacrylate and cationic surfactants has been studied. Aggregation numbers of dodecyltrimethylammonium (DoTA+) micelles formed in very dilute aqueous solutions of polyacrylate have been estimated with time-resolved fluorescence quenching, using as quencher dodecylpyridinium ion, which is distributed similar to DoTA+ between micelle and water subphases. The aggregation numbers (=65) were found to be the same as in 50 mM dodecyltrimethylammonium bromide (DoTAB) solutions. The distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
274
1
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(308 citation statements)
references
References 0 publications
27
274
1
1
Order By: Relevance
“…This reduces the tendency to associative phase separation. The salt effects have been confirmed for mixtures of cationics with NaPa (sodium poly(acrylate)) by (Hansson and Almgren, 1994). They suggested that the increasing cec with increasing surfactant chain length could be attributed to a larger aggregation number of micelles.…”
Section: Effect Of Saltmentioning
confidence: 90%
See 2 more Smart Citations
“…This reduces the tendency to associative phase separation. The salt effects have been confirmed for mixtures of cationics with NaPa (sodium poly(acrylate)) by (Hansson and Almgren, 1994). They suggested that the increasing cec with increasing surfactant chain length could be attributed to a larger aggregation number of micelles.…”
Section: Effect Of Saltmentioning
confidence: 90%
“…The N agg values for polyelectrolyte-bound aggregates increase with the surfactant chain length as in polymer-free systems (Almgren et al, 1992), but decrease with temperature (Hansson and Almgren, 1995) and are independent of the nature of the surfactant counterion (Hansson and Almgren, 1994) and of the added electrolyte (Hansson and Almgren, 1995). Thus, there is series of results in contrast with the behaviour of polymer-free surfactant solutions.…”
Section: Effect Of Saltmentioning
confidence: 93%
See 1 more Smart Citation
“…The pyridinium and trimethylammonium head groups are similar in many aspects, such as the central atom. Therefore, ideal mixing of CPC and CTAC has been assumed experimentally and theoretically [57,58,60,61]. Small deviations from ideality will be expected for DDPC and CTAC mixing, because of the four-carbon difference in their tails.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, cetyltrimethylammonium chloride (CTAC), which is not a PAH selective fluorescence quencher but with similar properties to CPC and DDPC, is used as a cosurfactant. The presence of CTAC allows the quencher concentration in micellar phase to be adjusted with little change to micelles [41,57,58].…”
Section: Introductionmentioning
confidence: 99%